Analysis of the Company's Long-Term Financial Management Policy Performance (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research was conducted using five-year financial reports from 2015 to 2019 from a company engaged in the basic chemicals sector. The analytical method used was financial ratio analysis. Company management is responsible for managing the company profitably, and management needs to understand and analyze the company's performance over a certain period of time to correct errors in decisions and maintain existing strengths. This financial performance research was conducted at PT Barito Pacific Tbk, which operates in the basic chemicals industry. The analysis found problems, namely, that long-term debt and company equity have increased, but through the calculation of the TIE ratio, the company's ability to pay interest expenses is still low. This forces management to implement certain strategies, both in exploiting available opportunities by utilizing existing strengths within the company, and strategies to mitigate the negative impact of potential external threats. By improving financial performance, such as making efficient use of long-term debt, the company's interest expense is not large, and it is hoped that the company's TIE will increase. Efforts to increase productivity and efficiency to achieve resilience and competitiveness must be carried out so that the utilization of all company resources reaches an optimal point.
Keywords: Asset Management; Funding; Productivity; Profitability